Ventriloquizing: Study of the Discursive Phenomenon and its Uses - Portillo-Fernández, Jesús (2018)
This paper is meant to look into the discursive phenomenom of ventriloquizing clarifying, first, the relationship and distinction between polyphony concept and others nearby as dialogism, heteroglossia and dialectic. Starting from the diachronic review of the concept, we study the facets of speaker and the communication situations involved into the different polyphonic discourses, distinguishing four kinds of polyphonic utterances: 1) reported speech, 2) echoic utterances, 3) intertexts and 4) ventriloquizing. We present a detailed description of the main characteristics of ventriloquizing (mimesis, semantic enrichment, possible change of voice –timbre and intonation–, linguistic function and recontextualization). Finally, attending to the two types of ventriloquizing (real and simulated), we propose a classification of the frequent uses based on four factors related to communications agents.